Ethical Cultures in Perinatal Care: Do They Exist? Correlation of Provider Attitudes with Periviability Practices at Six Centers - Lawrence, Christin; Laventhal, Naomi; Fritz, Katie A.; Carlos, Christine; Famuyide, Mobolaji; Tonismae, Tiffany; Hayslett, Drew; Coleman, Tasha; Jain, Meenu; Edmonds, Brownsyne Tucker; Leuthner, Steven; Andrews, Bree; Feltman, Dalia M. (American Journal of Perinatology, 2020)
Objective This study aimed to compare attitudes of providers regarding perinatal management and outcomes for periviable newborns of caregivers at centers with higher resuscitation (HR) and lower resuscitation (LR) rates in the delivery room.Study Design All obstetric and neonatal clinical providers at six U.S. sites were invited to complete an anonymous online survey. Survey responses were compared with clinical data collected from a previous retrospective study comparing centers' rates of planned resuscitation. Responses were analyzed by multivariable logistic and linear regression to assess how HR versus LR center respondents differed in management preferences and outcome predictions.Results Paradoxically, HR versus LR respondents, when adjusting for other variables, were less likely to respond that interventions such as antenatal steroids (odds ratio: 0.61, 95% confidence interval [CI]: 0.42–0.88, p < 0.009) and resuscitation (OR: 0.59, 95% CI: 0.44–0.78, p < 0.001) should be given at 22 weeks. HR versus LR respondents also reported lower likelihood of survival and acceptable quality of life (OR: 0.7, 95% CI: 0.53–0.93, p = 0.012) at 23 weeks.Conclusion Despite higher rates of planned resuscitation at 22 and 23 weeks, steroid usage and survival rates did not differ between HR and LR sites. In this subsequent survey, respondents from HR centers had a less favorable outlook on interventions for these newborns than those at LR centers, suggesting that instead of driving practices, attitudes may be more closely associated with experiences of clinical outcomes.
Keywords: neonatology; decision-making; ethics; attitudes